2013
DOI: 10.1590/s1980-65742013000400006
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring muscle damage markers during a four-week downhill walking exercise program

Abstract: Abstract-Eccentric-based exercise is known to induce muscle damage (MD). The purpose of this study was to investigate effect of downhill walking (DW) sessions on MD and aerobic markers in young adults. Eight male subjects were submitted to a 4-week DW periodized exercise program. Subjects' soreness (SOR) was assessed each training day. Serum creatine quinase activity (CK) was collected before the first training session, and at the end of each of the four weeks. Oxygen uptake (VO 2 ) and perceived exertion (PE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In our study, alterations in four frequently assessed EIMD markers (SOR, CIR, ROM and CMJ) were identified throughout the competition. However, an addition effect might have led to greater changes in EIMD markers that would not be manifested after a single match, as previously described in a similar model 22 . However, considering that the most important TH competitions have a short-term, condensed characteristic 23 , it is also important to investigate the level of stress imposed to the neuromuscular system throughout them.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In our study, alterations in four frequently assessed EIMD markers (SOR, CIR, ROM and CMJ) were identified throughout the competition. However, an addition effect might have led to greater changes in EIMD markers that would not be manifested after a single match, as previously described in a similar model 22 . However, considering that the most important TH competitions have a short-term, condensed characteristic 23 , it is also important to investigate the level of stress imposed to the neuromuscular system throughout them.…”
Section: Discussionmentioning
confidence: 64%
“…However, although no significant differences were found, CMJ presented a slight decrease on the first day of competition, remaining below baseline values up to the third day and, finally, falling to a significantly different level on the fourth day. We believe that this significant decrease might have occurred due to the aforementioned addition effect 22 , in which subsequent ruptures on the muscular ultra-structural components kept weakening the athletes' muscles up to a point in which it produced significant less power and, consequently, a shorter jump height. It is important to state that assessments were performed with athletes jumping with both limbs.…”
Section: Discussionmentioning
confidence: 99%
“…The training protocol started at a walking speed of 5.0 km/h for DWG and 4.5 km/h for LWG, with increments of 0.5 km/h every week. The initial speeds were not similar between groups due to dif-ferences in the metabolic requirements for level and downhill walking 17 , and were set based on a pilot study. Oxygen uptake was continuously assessed during the final training session of each week for both groups using a pulmonary gas exchange analyzer (Cosmed Quart PFTergo, Rome, Italy).…”
Section: Trainingmentioning
confidence: 99%
“…Even though a protective phenomenon known as repeated bout effect is obtained after the occurrence of EIMD, blunting the damaging response after other sessions, compliance to training sessions that elicit high magnitude of EIMD is low 13 . Recent studies have shown that downhill walking (DW) can be considered an alternative to downhill running [14][15][16][17] . Indeed, Lima et al 17 demonstrated that a 4-week periodized DW training program induced moderate magnitudes of EIMD, suggesting that DW can be adopted as training stimulus without impairing further sessions.…”
Section: Introductionmentioning
confidence: 99%